Adoption of Livestock Insurance among Dairy Farmers at Chitwan, Nepal - Poudel, Sudip; BC, Lalit; Shrestha, Santosh; Subedi, Sanjiv (Nepalese Journal of Agricultural Sciences, 2026)
Natural calamities, disease and pest, and unpredictable weather possess a high risk in livestock farming and cost a heavy loss to the farmers. Livestock insurance is one of the important strategies to reduce the risks related to livestock production. To assess the adoption process and impact of livestock insurance on dairy farmers, a study was conducted at Chitwan district among the 98 farmers (insured and non insured) sampled using stratified random sampling. Descriptive statistics were used to analyze the socio-economic and demographic variables of insurer and non-insured farmers. Pro bit model regression was used to analyze the impact of different variables on adoption of livestock insurance. In addition, t-test was also done to compare the numeric mean value of the variables of two categories of respondent, insured and non-insured. The Pro bit model results revealed that the age, gender, income from livestock, awareness about insurance and awareness of subsidy on insurance have a significant (p<.05) effect on the adoption of livestock insurance. The result of Chi-square test suggests that members of a farmers group/cooperatives, subsidy, loan and members of community agents have a significant (p<.05) effect on the adoption of the livestock insurance. The study underscores the need for a strategic policy to promote livestock insurance in Chitwan district. Both the government and non-life insurance companies must prioritize enhancing farmer awareness and understanding through targeted advertising and training to establish credibility and reliability. These findings will be helpful for the improvement of different livestock insurance policy and programs implemented by different government bodies and insurance companies.